Culture and youth in public spaces: the SLAM experience - Castro , Gabriela Longatti; Matos, Gabriela Santos de; Batista, Soares dos Santos; Oliveira, Rodrigo Ribeiro de (Brazilian Journal of Production Engineering, 2023)
Slam is a poetic and verbal action that was greatly influenced by the hip-hop movement. The Slam is a cultural event that promotes social transformations with urban and peripheral youth as protagonists. The article presents an initial knowledge about Slam in the United States and Brazil, contextualizing its emergence and specificities considering the experience in urban contexts, especially in a city in the interior of the State of São Paulo. The objective of the study is to present and analyze the potential of Slam as a factor of expression for urban youth, pointing out ways for the sociocultural and educational insertion of young people. The research is bibliographical and empirical in nature based on the immersion of the authors in this cultural and educational practice.
Keywords: Slam.; Culture and education.; Youth; Education and culture